DETERMINASI NILAI PERUSAHAAN: PERAN STRUKTUR MODAL, RISIKO KEUANGAN, DAN KEPEMILIKAN MANAJERIAL - Umayah; Intan Rahma Sari (Jurnal Akuntansi Dan Manajemen, 2026)
This study aims to analyze the effect of capital structure, financial risk, and managerial ownership on firm value. Firm value is proxied by Price to Book Value (PBV), while the independent variables include capital structure, financial risk, and managerial ownership. The population of this study consists of property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sampling technique used is purposive sampling, resulting in nine companies as the research sample. The data were analyzed using panel data regression with EViews 12 software, including descriptive statistical analysis, classical assumption tests, model selection (Common Effect Model, Fixed Effect Model, and Random Effect Model), and hypothesis testing. The results indicate that capital structure, financial risk, and managerial ownership simultaneously affect firm value. However, partially, only financial risk has a significant effect on firm value, while capital structure and managerial ownership do not have a significant effect. These findings suggest that financial risk is a key factor considered by investors in evaluating firm value, particularly in the property and real estate sector.